Weight-status Related Differences in Reflective and Impulsive Determinants of Physical Activity in Youngsters (8–18 years old) - Gill A. ten Hoor (Health Psychology Bulletin, 2020)
Objective: To investigate associations between weight status and physical activity, psychosocial impulsive, and reflective determinants of exercise behavior in youngsters (8–18 years old), distinguishing between strength exercises and aerobic exercises. Method: Cross-sectional survey of 133 youngsters (89 girls – 59 youngsters who are being treated for obesity in an outpatient lifestyle intervention program, plus 74 youngsters from the general population). In order to identify reflective determinants, participants completed questionnaires. For the impulsive determinants, participants completed two computerized reaction time sorting-tasks (‘Implicit Association Tests’). Results: Exercise intentions, including those for aerobic and strength exercises, were positively correlated with BMI z-scores. Youngsters with a higher BMI z-score often reported that their friends think they should exercise and were more confident that they could exercise more if they wanted to. No other determinants, including impulsive determinants, were correlated with BMI z-scores. Conclusion: In terms of reflective determinants, few differences were found between youngsters with higher BMI z-scores as compared to youngsters with lower BMI z-scores. There was no significant correlation between BMI z-score and the impulsive determinants of aerobic versus strength exercise. This suggests that youngsters, independent from weight status feel that they could be reached by the same kind of physical activity intervention.